Nonspecific abnormal genital discharge. - Ortega G., Lizardo (2015)
In this paper, we also give a conventional meaning and usually accepted by nonspecific flow; being called him so, to that produced by microbial agents septic, infection such as staphylococcus, streptococcus, Escherichia coli, etc .; and considering specific flow, as produced by the gonococcus, the trichomonas, Monilia, Haemophilus, viruses, etc.